Integration of Monitoring Systems for Tourist Destinations into National Environmental Monitoring Systems - KOLTUNOVA, Yuliya I.; TKACHEV, Aleksandr A.; TOLMACHEVA, Svetlana V. (Journal of Environmental Management and Tourism, 2019)
Monitoring the state of a tourist destination is determined by the fact that each site must not only have an infrastructure of the appropriate type, but also maintain an equilibrium ecological state, which is determined by whether human activities are either minimized or not implemented at all. In the regions of the Arctic, this interaction is also due to the fact that a significant part of eco-tourism is organized in a location dominated by water tourism. In accordance with this, we define the actual formation of a model of monitoring a water body as based on ecological tourism in the Arctic regions. The novelty of the proposed research is determined by such a factor, which forms an assessment of the quality of the environmental monitoring carried out in order to fully realize the possibility of reducing the anthropogenic load. The authors have developed a strategy, model and practical application for ecosystems based on the use of hydro resources. The application of the obtained results is possible in those ecosystems that are exposed to intense effects and may experience a decrease in recreational capacity. The authors show that the developed model can be fully implemented in the territories, which currently can offer tourists rest in hydrozones, but due to the high load they cannot always accept a sufficient number of tourists.